A STUDY OF THE SYNTHESIS OF HYBRID ORGANOSILICATE NANOTUBES - Eko Sri Kunarti; Grainne M Moran (Indonesian Journal of Chemistry, 2005)
Hybrid organosilicate nanotubes have been prepared by sol-gel chemistry, using crystalline ammonium tartrate as the tube-forming template. The nanotubes were prepared by controlled hydrolysis and co-condensation of tetraethyl orthosilicate (TEOS) and methyltriethoxysilane (MTES) at room temperature. The synthetic conditions have been systematically studied. The physical characteristics of the materials were examined by scanning electron microscopy (SEM) and the aging times of the tubes due to slow post-gelation condensation reactions was investigated. The morphology and microstructure of the nanotubes are greatly influenced by the synthetic conditions.